Evaluation of the effect of etching with ytterbium fiber laser on the bond strength, color stability, and fracture analysis of lithium disilicate ceramics to bovine teeth: an in vitro study - Göknil Alkan Demetoğlu; Esra Talay Çevlïk (BMC Oral Health)
Abstract Purpose This study aimed to investigate the impact of 1070 nm Ytterbium Fiber Laser (YFL) on the shear bond strength of lithium disilicate ceramics to enamel. Methods Fifty-four freshly extracted bovine teeth were embedded in acrylic resin, with labial surfaces exposed. The teeth underwent etching with phosphoric acid, followed by the application of bond resin. Ceramic samples of 0.5 mm, 1 mm, and 1.5 mm thickness were obtained from lithium disilicate CAD blocks using a precision cutting tool. Samples were divided into two subgroups according to surface treatment method: one group was treated with 4.5% hydrofluoric acid for 20 s, while the other was treated with a 20 W average power YFL. One sample from each subgroup underwent SEM analysis; the remaining samples were cemented to prepared bovine teeth using composite resin cement. Color measurements were performed before and after surface treatments. Shear bond strength was evaluated using a universal testing machine with a crosshead speed of 0.5 mm/min. Fracture analyses were conducted using a stereomicroscope. Statistical analyses were performed using two-way ANOVA and two-way ANOSIM. Results According to the two-way ANOVA results, the ΔE00 values were significantly higher in all thickness groups treated with YFL than in those subjected to acid treatment. Two-way ANOSIM revealed that neither sample thickness nor surface treatment had a statistically significant effect on shear bond strength. SEM analysis revealed micro-roughness in the acid-treated samples and mini-laser spots in the laser-treated groups, and no microfractures or cracks detected in any of the groups. Conclusion The shear bond strengths of lithium disilicate ceramics, whether treated with YFL or hydrofluoric acid, were found to be comparable. These findings suggest the potential utility of 1070 nm YFL for ceramic etching, supporting the need for further investigation in dental applications.